Effects of whole-body cryostimulation exposure in sport and medicine - Hausswirth, C. (ASPETAR Sports Medicine Journal, 2015)
Elite athletes often train intensitively or compete over consecutive days. Cumulative fatigue over such periods of training or competition can reduce athletic performance. Adequate recovery between training sessions and/or competitive events is therefore essential to minimise the risk of fatigue and optimise performance. In this context, the use of whole-body cryotherapy (WBC) as a tool to aid recovery shows benefits on some inflammatory parameters, possible improvement of antioxidant status and improvements in mood and mild depression. Heating the body is supposed to be beneficial to athletes' recovery, to treat muscle pain and as part of rehabilitation after injury. It has been already demonstrated that WBC stimulates the physiological reactions of an organism which results in analgesic, anti-swelling, antalgic immune and circulatory system reactions and could improve recovery after muscular trauma injury. Definition is needed as to the precise context in which athletes may use this tool to optimise recovery in relation to improving sleep patterns, optimising the parasympathetic system and increasing their general well-being.